Rove beetles (Coleoptera: Staphylinidae) associated with Aenictus laeviceps (Hymenoptera: Formicidae) in Sarawak, Malaysia: Strict host specificity, and first myrmecoid Aleocharini - Maruyama, Munetoshi; Matsumoto, Takashi; Itioka, Takao (Zootaxa, 2011)
The fauna of myrmecophilous rove beetles associated with Aenictus laeviceps (sensu Wilson 1964) at Lambir Hills National Park, Sarawak, Malaysia was investigated. Eight species belonging to six genera of the subfamily Aleocharinae including the following new taxa are recorded and/or described: Myrmecosticta exceptionalis Maruyama gen. et sp. nov., Aenictocleptis hirsutoides Maruyama sp. nov., Aenictocleptis lambirensis Maruyama sp. nov., Mimaenictus matsumotoi Maruyama sp. nov., Procantonnetia opacithorax Maruyama sp. nov., Weissflogia pubescens Maruyama sp. nov. Three morphotypes (L1, L2 and S) are recognized in A. laeviceps, and strict host specificity by the rove beetles for the morphotypes was observed. Myrmecosticta exceptionalis is the first known myrmecoid species of the tribe Aleocharini and belongs to the Tetrasticta generic group.